Impact of the COVID-19 pandemic on training and technology use among Chilean amateur athletes - Natalia Chahin-Inostroza; Fanny Bracho-Milic; Edith Velasco-Bahamonde; Claudia Navarrete-Hidalgo; Pamela Serón; Pamela Serón (Frontiers Media S.A., 2024)
IntroductionThe COVID-19 pandemic was a health problem which affected the entire world. Sports were strongly affected, especially outdoors. The purpose of this study was to evaluate the impact of COVID-19 pandemic on training and technology use among Chilean amateur athletes.MethodAn observational descriptive cross-sectional study, carried out during the 2021-2. Nonprobabilistic convenience sample of people over 18 years. Data were obtained via online survey and analyzed with Stata 16.0 statistical program for runners, triathletes, cyclists.ResultsThe sample was 179 athletes, average age was 42.5 years ±10.2; males were 58.6%. 22.65% of the sample were triathletes, 58% runners, and 18.2% cyclists. Training habits were measured during Pre-Pandemic (PP), Pandemic With Quarantine (PWQ), and Pandemic Without Quarantine (PWOQ). In total sample, a decrease was observed in variables of average training frequency of 1.28 sessions per week (p = 0.001; d = 0.648); weekly average training time of 189.63 min (p = 0.005; d = 0.293); days per week with high and medium intensity training of 0.95 (p = 0.001; d = 0.833) and 0.37 (p = 0.001; d = 0.327) respectively; and days per week with cardio training of 1.01 (p = 0.001; d = 0.678), comparing the PP and PWQ periods. When comparing PWQ and PWOQ, an increase was observed in the same variables mentioned above of 1,57 sessions per week (p = 0.001; d = 0.513); 162.68 min per week (p = 0.020; d = −0.245); days per week with high of 0.82 (p = 0.001; d = −0.714) and medium intensity training of 0.46 (p = 0.001; d = −0.412); days per week with cardio training of 1.14 (p = 0.001; d = −0.730); and included strength training of 0.42 (p = 0.012; d = −0.312). For technology incorporation, over 78% (p = 0.023) claimed to used devices to measure training, with the watch being the preferred device in over 72% (p = 0.002) during the three timeframes. Highlighted the rise in use of training software during and after the lockdown period of more than 23% (p < 0.001).DiscussionAll variables related with training habits decreased comparing PP and PWQ and all variables rose between PWQ and PWOQ; however, comparing PP and PWOQ, there are small differences, which do not always favor the PWOQ, reflecting how athletes have not yet been able to recover their training rhythms. Finally, we should note that the use of technology increased, in all periods.